REVIEW OF THE PRINCIPLES OF SIYASAH DUSTURIYYAH REGARDING THE REGULATION OF THE IMPLEMENTATION OF THE PEOPLE'S HOUSING SAVINGS (TAPERA) - Zalfaa Salsabila (Jurnal Al Tasyri'iyyah, 2025)
This study aims to discuss a review of the principles of Siyasah Dusturiyyah regarding regulations on the implementation of the People's Housing Savings Program. This study is qualitative in nature. The research design is a literature study. The results show that the problems detected in the Tapera implementation regulations indicate a discrepancy with the principles of Siyasah Dusturiyyah. Contradictions with the principles of musyawarah (syura), substantive justice (al-‘adl), public interest (maslahah), and obedience to valid law (tha‘at li al-imam) are certainly violated. This shows that the objectives of Tapera have not been achieved as expected.